PEMBANGUNAN WEB E-COMMERCE B2B UNTUK MENINGKATKAN PEMASARAN PRODUK MENGGUNAKAN LINEAR SEQUENTIAL MODEL - Nunung Hidayatun; Susafaati Susafaati; Hidayanti Murtina (Paradigma, 2020)
Internet causes trading activities to develop, namely by the existence of online product sales, this facility is called e-commerce. PT. Victoria Label is a PMA (Foreign Investment) company engaged in making woven labels and printed labels (printing labels), seal logos, and leather embosses, which of course are eager to get far greater profits by increasing product marketing. However, the business processes currently being implemented are fairly conventional, such as exhibitions, telephone sales, e-mails and other promotional media which have an impact on the high costs incurred and are considered to be less effective and efficient. Therefore, e-commerce web development at PT Victoria Label is deemed necessary to help improve the company's progress, using the Linear sequential model in the design of information systems. The results of this study are the application of e-commerce with B2B models to control business processes and to bring various efficiency of operational activities to the company. Keywords: E-Commerce, B2B, Linear sequential model, system design.